Introducing the Self‐Cleaning FiLtrAtion for Water quaLity SenSors (SC‐FLAWLeSS) system. (11th July 2020) - Khandelwal, Aashish; González‐Pinzón, Ricardo; Regier, Peter; Nichols, Justin; Van Horn, David J.
Abstract: Sensor‐based, semicontinuous observations of water quality parameters have become critical to understanding how changes in land use, management, and rainfall‐runoff processes impact water quality at diurnal to multidecadal scales. While some commercially available water quality sensors function adequately under a range of turbidity conditions, other instruments, including those used to measure nutrient concentrations, cease to function in high turbidity waters (> 100 nephelometric turbidity units [NTU]) commonly found in large rivers, arid‐land rivers, and coastal areas. This is particularly true during storm events, when increases in turbidity are often concurrent with increases in nutrient transport. Here, we present the development and validation of a system that can affordably provide Self‐Cleaning FiLtrAtion for Water quaLity SenSors (SC‐FLAWLeSS), and enables long‐term, semicontinuous data collection in highly turbid waters. The SC‐FLAWLeSS system features a three‐step filtration process where: (1) a coarse screen at the inlet removes particles with diameter > 397 μ m, (2) a settling tank precipitates and then removes particles with diameters between 10 and 397 μ m, and (3) a self‐cleaning, low‐cost, hollow fiber membrane technology removes particles ≥ 0.2 μ m. We tested the SC‐FLAWLeSS system by measuring nitrate sensor data loss during controlled, serial sediment additions in the laboratory and validated it by monitoring soluble phosphate concentrations in the arid Rio Grande river (New Mexico, U.S.A.), at hourly sampling resolution. Our data demonstrate that the system can resolve turbidity‐related interference issues faced by in situ optical and wet chemistry sensors, even at turbidity levels > 10, 000 NTU.